CARACTERISATION PHYSICO-CHIMIQUE DES EAUX SOUTERRAINES DES SOURCES NON AMENAGEES DE LA COMMUNE DE KISANGANI DANS LA VILLE DE KISANGANI EN REPUBLIQUE DEMOCRATIQUE DU CONGO - Nathan, IUNGBI SINGA; Wafi, WANSENDE FIASOLUA; Alain, BULUKU EKWAKWA (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2025)
In view of the population explosion, the population is turning to the use of spring water in urban, peri-urban and rural areas because water coverage by designated services is becoming increasingly difficult. However, these waters, often not treated or controlled to determine their quality in relation to the potability standards set by the WHO, frequently present quality problems and can cause very serious environmental damage to humans, animals and plants that consume them. This study proposes an in-depth physico-chemical analysis capable of assessing the quality of these undeveloped spring waters in the commune of Kisangani in the city of Kisangani, capital of the Tshopo Province in the Democratic Republic of Congo in order to better inform the user population. This is why, in this study, we evaluated parameters such as: pH, temperature, conductivity, TDS, dissolved oxygen, color, odor, chlorine and turbidity, sulfate, nitrite and nitrate, phosphate, some heavy metals, etc.